A Benzooxazole‐Based Probe for the Sensitive Detection of Hydrogen Sulfide: Kinetic and Transition‐State Studies and In Vitro Application in HepG2 Cells. Issue 25 (3rd July 2018) - Pal, Kaberi; Islam, Abu Saleh Musha; Prodhan, Chandraday; Bhunya, Sourav; Paul, Ankan; Ali, Mahammad
Abstract: A benzooxazole based probe, 2‐[4‐(2,  4‐dinitrophenoxy)‐phenyl]‐benzooxazole has been synthesized and thoroughly characterized by mass, 1 H‐NMR and FT‐IR spectroscopy. The probe exhibits sensitive and selective response towards H2 S in DMSO:PBS buffer (6:4, v/v, pH 7.4) over the other reactive sulfur species especially the biological thiols like cysteine, homocysteine and glutathione. Due to thiolysis of dinitrophenyl ether, this probe displays turn‐on fluorescence response where the sensing mechanism follows inhibited photoinduced electron transfer (d‐PET) process. This thiolysis reaction proceeds through aromatic nucleophilic substitution (SN Ar) type mechanism. Moreover, the transition state study shows that this process is exoergic with favorable energy barrier of 5.0 kcal/mol. The kinetic studies of the probe with HS – at various pH assist to evaluate the acid dissociation constant value ( K a 1 =1.09 × 10 −8 M −1 ) of H2 S that illustrate a reasonable agreement with the literature value, K a (9.5 x 10 −8 M −1 ). Finally, this probe is cell permeable, non‐cytotoxic and suitable for intracellular cytoplasmic HS – sensing in live cells with a very low detection limit (51.8 nM). Abstract : A benzooxazole based moiety, 2‐[4‐(2,  4‐dinitrophenoxy)‐phenyl]‐benzooxazole, DPPB, displays sensitive and selective turn‐on fluorescence response towards H2S due to inhibited photoinduced electron transfer (d‐PET) process. This thiolysis reaction shows the first order rate dependence on both the probe and HS–. The reaction follows the aromatic nucleophilic substitution (SN Ar) type mechanism which is confirmed by TS‐study with suitable energy calculation. This cell permeable, non‐cytotoxic probe is suitable for intracellular cytoplasmic HS– sensing in live cells.